Direct costs of illness of patients with chronic cough in rural Malawi—Experiences from Dowa and Ntchisi districts - Sichali, Junious M. (PLoS One, 2019)
INTRODUCTION: Chronic cough is a distressing symptom and a common reason for people to seek health care services. It is a symptom that can indicate underlying tuberculosis (TB) and/or chronic airways diseases (CAD) including asthma, chronic obstructive pulmonary disease (COPD) and bronchiectasis. In developing countries including Malawi, provision of diagnostic services and clinical management of CAD is rudimentary, so it is thought that patients make costly and unyielding repeated care-seeking visits. There is, however, a lack of information on cost of illness, both direct and indirect, to patients with chronic cough symptom. Such data are needed to inform policy-makers in making decisions on allocating resources for designing and developing the relevant health care services to address universal coverage programmes for CAD. This paper therefore explores health seeking costs associated with chronic cough and explores information on usage of the coping mechanisms which indicate financial hardship, such as borrowing and selling household assets. METHODS: This economic study was nested within a community-based, population-proportional cross-sectional survey of 15,795 individuals aged 15 years and above, in Dowa and Ntchisi districts. The study sought to identify individuals with symptoms of chronic airways disease whose health records documented at least one of the following diagnoses within the previous year: TB, Asthma, COPD, Bronchitis and Lower Respiratory Tract Infection (LRTI). We interviewed these chronic coughers to collect information on socioeconomic and socio-demographic characteristics, health care utilization, and associated costs of care in 2015. We also collected information on how they funded their health seeking costs. RESULTS: We identified 608 chronic coughers who reported costs in relation to their latest confirmed diagnosis in their hand-held health record. The mean care-seeking cost per patient was US$ 3.9 (95% CI: 3.00–5.03); 2.3 times the average per capita expenditure on health of US$ 1.69. The largest costs were due to transport (US$ 1.4), followed by drugs (US$ 1.3). The costs of non-medical inputs (US$ 2.09) was considerable (52.3%). Nearly a quarter (24.4%) of all the patients reportedly borrowed or/and sold assets/property to finance their healthcare. CCs with COPD and LRTI had 85.6% and 62.0% lower chance of incurring any costs compared with the TB patients and any patients with comorbidity had 2.9 times higher chance to incur any costs than the patients with single disease. COPD, Bronchitis and LRTI patients had 123.9%, 211.4% and 87.9% lower costs than the patients with TB. The patients with comorbidity incurred 53.9% higher costs than those with single disease. CONCLUSIONS: The costs of healthcare per chronic cougher was mainly influenced by the transport and drugs costs. Types of diseases and comorbidity led to significantly different chances of incurring costs as well as difference in magnitude of costs. The costs appeared to be unaffordable for many patients.